2021
DOI: 10.1029/2021gc010004
|View full text |Cite
|
Sign up to set email alerts
|

Rock Magnetic Signature of Heterogeneities Across an Intraplate Basal Contact: An Example From the Northern Apennines

Abstract: Plate boundaries at shallow depth are complex and highly deformed zones showing structures from both distributed and localized deformation (Collot et al., 2011;Sibson, 2013). Depending on the heterogeneity of the rock assemblage (i.e., competent vs. incompetent materials and/or clay contents) within the shear zone and the strain rates, shearing can be localized along discrete faults during seismic slip, while aseismic slip produces a scaly fabric associated with distributed deformation (Fagereng & Sibson, 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 100 publications
(180 reference statements)
0
4
0
Order By: Relevance
“…It is used to determine the saturation magnetization, coercivity and remanence of rock samples to analyze the influence of seismic slip-on rock magnetism. Robustelli et al [ 18 ] measured the Thermomagnetic susceptibility curves of the sample by heating the sample to 700 °C, and then cooling it to room temperature to measure the magnetic signature along interpolate sheet zones. Lund et al [ 19 ] tested the hysteresis loop of deep-sea sediment samples through the MicroMag cycle.…”
Section: Introductionmentioning
confidence: 99%
“…It is used to determine the saturation magnetization, coercivity and remanence of rock samples to analyze the influence of seismic slip-on rock magnetism. Robustelli et al [ 18 ] measured the Thermomagnetic susceptibility curves of the sample by heating the sample to 700 °C, and then cooling it to room temperature to measure the magnetic signature along interpolate sheet zones. Lund et al [ 19 ] tested the hysteresis loop of deep-sea sediment samples through the MicroMag cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as noted by Borradaile (1988) “magnetic fabrics should not be used for routine methods of ‘strain analysis’ without further study” as for example, composite fabrics of sedimentary, compaction and tectonic origin can result in distinct AMS due to lithology based differences in strain partitioning (Evans et al., 2003). All together this establishes the necessity to combine magnetic studies with microstructural, mineral chemistry and geochemical characterization as the relationship between fault or SZ kinematics and dynamics can be individual (Kusbach et al., 2019; Narloch et al., 2021; Robustelli Test & Zanella, 2021; Yang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the magnetic properties of fault rocks could offer valuable insights into physical and chemical processes affecting fault rocks. The available rock magnetic studies on fault rocks from seismically active zones have demonstrated that magnetic properties of fault rocks could shed lights on strain geometry, seismic frictional heating, fluid infiltration, and so on (Chou et al., 2012a, 2012b, 2020; Ferré et al., 2012, 2014, 2017; Greve et al., 2020, 2021; D. Liu et al., 2014; Robustelli Test & Zanella, 2021; Yang et al., 2012, 2018, 2019; Yang, Yang, et al., 2016; L. Zhang et al., 2018; for a review, see Yang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The available rock magnetic studies on fault rocks from seismically active zones have demonstrated that magnetic properties of fault rocks could shed lights on strain geometry, seismic frictional heating, fluid infiltration, and so on (Chou et al, 2012a(Chou et al, , 2012b(Chou et al, , 2020Ferré et al, 2012Ferré et al, , 2014Ferré et al, , 2017Greve et al, 2020Greve et al, , 2021D. Liu et al, 2014;Robustelli Test & Zanella, 2021;Yang et al, 2012Yang et al, , 2018Yang et al, , 2019L. Zhang et al, 2018; for a review, see Yang et al, 2020).…”
mentioning
confidence: 99%